Peran Gerakan Women Wage Peace dalam Upaya Perdamaian Israel-Palestina: Studi Tentang Diplomasi Akar Rumput oleh Perempuan - Mutmainah, Ghaida Syarifah; Mahdi, Imam (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
The Israeli-Palestinian conflict has been ongoing for decades with complex, multidimensional impacts. However, traditional diplomatic approaches dominated by state and military actors often reach a dead end. In this context, the Women Wage Peace (WWP) movement, born after the 2014 Gaza War, emerged as a grassroots diplomatic force driven by women across ethnicities, religions, and political orientations in Israel. This study aims to analyze WWP's role and contribution in promoting peace through a gender-based and participatory approach. Using qualitative methods with a descriptive approach, this study explores WWP's activities and strategies based on organizational documentation, publications, and theoretical studies on grassroots diplomacy and UNSC Resolution 1325. The study results show that WWP has not only succeeded in building public awareness and political pressure through symbolic actions such as the Peace Train and March of Hope, but also established a cross-community network with Palestinian women through organized collaboration, regular dialogue, and joint actions such as the WWP – Women of the Sun declaration. This network enables the creation of relationships of trust and direct cooperation between citizens, which then become a driving force for social transformation. WWP emphasizes that women are not only victims of conflict but also key agents in creating sustainable peace. These findings highlight the importance of incorporating women-based grassroots diplomacy into peace policies in conflict zones.